Hubungan Antara Pengetahuan Kebakaran dan Masa Kerja terhadap Unsafe Action Kebakaran pada Karyawan PT. X - Alif Faiq Hernanda; Bachtiar Chahyadi; Sri Mulyani (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
Fire unsafe actions can be influenced by the driving factors of the workers themselves, including fire knowledge and work period, then the knowledge and work period of a person can trigger a behavior. This study aims to analyze the relationship between fire knowledge and tenure on fire unsafe actions in PT. X employees.This research is an analytic observational study, with a cross sectional approach. The population in this study were workers totaling 200 workers, then from this population 80 research respondents were obtained with a sampling technique using simple random sampling. This study used a questionnaire of fire knowledge variables and tenure and unsafe actions as data collection instruments. The data analysis technique used is the Somers'D test to test whether there is a relationship or not after being tested for ordinal logistic regression. The results of the ordinal logistic regression test show that the fire knowledge and tenure variables analyzed are significantly related to unsafe fire actions, p value = 0.000, and have decreased in -2 log likelihood. Fire knowledge has a wald value of 30.449 while the working period only has a wald value of 14.526 so that from the wald value it can be concluded that fire knowledge is a variable that is very influential on fire unsafe actions. The result of Nagelkerke R-Square is 0.494 (49.4%) this basis states that the independent variable is able to explain the dependent variable by 49.4%. There is a significant relationship between fire knowledge and work period on fire unsafe actions among PT. X employees.